Design and Development of Servo Motor Controller for SoC-FPGA - Zainon, Mohd Zahiruddin; Mhd Poad, Hazwaj (Evolution in Electrical and Electronic Engineering, 2021)
An Field-Programmable Gate Array (FPGA) are fully programmable systems on a chip (SoC), capable of handling a wide range of tasks. The key characteristics of current FPGAs are first outlined and compared to those of previous generations. This project aims to develop a servo motor controller that is implemented on the FPGA and evaluate the motor controller system by its efficiency. The Verilog code of the controller will be generated containing the motor controller. The outputs of the controller will be observed by using Terasic DE10-Nano Development Kit. To develop the servo motor controller, firstly develop the Pulse Width Modulation motor for the controller and determine its functionality. Proceed to pin assignment for the inputs and outputs signal using Quartus II software and bump into the DE10-Nano board if no error occurred. The result will be obtained through software and hardware simulation. Motor controller output will be analysed from the waveform and LED test to test the servo motor controller.